2013
DOI: 10.1177/0040517513485624
|View full text |Cite
|
Sign up to set email alerts
|

A study on easy-care laundering of linen fabrics

Abstract: Linen fabrics are known for their superior comfort properties over fabrics of other origins. However, they have a very high tendency to wrinkle during use and laundry. In order to overcome this problem, easy-care finishes are applied on linen during or after fabric production. These chemicals are partially released during use and washing. Moreover, strengths of fabrics are affected negatively. Increasing ecological concerns and public awareness bring the need for an environmentally friendly alternative process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…It should be noted that both average shrinkage and average smoothness rating results reported are those measured after the third laundering, as it is known that the performance results for fabrics after multiple launderings are generally more significant as a result of their being loaded with extensive stress during manufacturing, and analysis of measured performances after multiple launderings would be more representative of the effects of the parameters studied. 22 Before presenting individual and interaction effects of steaming combinations, spinning levels, hot rinsing or hot softening on average shrinkage and average smoothness rating values, it will be shown that the two washing machines used in the study are identical in their performance in terms of their effect on resulting average shrinkage values and average smoothness ratings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that both average shrinkage and average smoothness rating results reported are those measured after the third laundering, as it is known that the performance results for fabrics after multiple launderings are generally more significant as a result of their being loaded with extensive stress during manufacturing, and analysis of measured performances after multiple launderings would be more representative of the effects of the parameters studied. 22 Before presenting individual and interaction effects of steaming combinations, spinning levels, hot rinsing or hot softening on average shrinkage and average smoothness rating values, it will be shown that the two washing machines used in the study are identical in their performance in terms of their effect on resulting average shrinkage values and average smoothness ratings.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Profile 7, which incorporates a steaming step after the last spin, is included in each profile, as one part of the steaming combination, which was previously shown to cause an additional decrease in shrinkage during laundering, superior to that offered when other steaming steps are considered individually. 22 The individual effects of heating (hot rinsing and hot softening), spinning (low, medium, and high), and steaming combinations (7-4, 7-5, and 7-6) on the average smoothness rating after the third laundering are shown in Figure 5. It is apparent that low-level spinning results in a slightly lower average smoothness rating (3.24) when compared with those of medium-and high-level spinning (3.31 and 3.33, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The orthogonal design of four factors at three levels was applied, and four key influencing factors-rotating speed, washing load size, spinning time, and fabric thickness-were identified in the literature. 6,7,14 Water temperature was excluded since top-loading washing machines in China always operate at room temperature because there is only a cold water system. The levels of corresponding factors were set according to the adjustable range of the washing machine.…”
Section: Experimental Details Design Of Experimentsmentioning
confidence: 99%
“…In recent years, with consumers' increasing need for easy care, researchers have gradually focused on the optimization of washing programs. Gocek et al 6 have improved the wrinkling behavior of linen fabrics during washing by selecting suitable levels of temperature, rate of mechanical action, revolution per minute, and water amount applied during laundering. Additionally, Shao and Yuan 7,8 have optimized washing programs for cotton shirts by regulating washing parameters, including washing temperature, drying time, rotating speed, and so on.…”
mentioning
confidence: 99%